Digital Transformation in the Customer Experience Consumer: A Systematic Review of the Scientific Literature between 2018 – 2022 (LACCEI, 2024)
This systematic review presents and analyzes various studies referred to Digital Transformation in the Consumer Experience, the general objective of is to determine topics related to Digital Transformation in the Consumer Experience during the last 5 years through a review and analysis of the selected articles. The databases used in the search for studies used in the work are Scopus, SciELO, ScienDirect, Web Of Science and EBSCO the inclusion and discard criteria of the work were chosen in order to obtain studies that allow the elaboration of a precise, concrete and quality research, these articles should have been published within the years 2018-2022. In conclusion, 4 aspects were identified that are related to the Digital transformation. Among those that stand out, the strategy digital, the value proposition, Big Data and the company relationship customer. The limitations of this work were the language and the small amount of investigations regarding the two variables